Vendometric analysis of perception of advertising by consumers of medicinal drugs - A. D. Yermolaeva, Lobuteva A.V, Zakharova O.V., Krivosheev S.A., Lobuteva L.A., (Opción, 2019)
The objective of this study is to develop a methodology for assessing the perception of advertising slogans by consumers of medicinal drugs.To assess the perception of advertising by consumers of medicines, a methodological approach to vendometric analysis has been developed and tested, which allows identifying, evaluating and predicting the reaction of consumers to the advertising of pharmaceutical products. Practical implementation of the results of the vendometric analysis can contribute to the success of the advertising campaign and the achievement of the organization’s objectives in meeting the needs of consumers.